Association of stem cell-related markers and survival in astrocytic gliomas - Wan, Feng; Herold-Mende, Christel; Campos, Benito; Centner, Franz-Simon; Dictus, Christine; Becker, Natalia; Devens, Frauke; Mogler, Carolin; Felsberg, Jörg; Grabe, Niels; Reifenberger, Guido; Lichter, Peter; et al. (Biomarkers, 2011)
To study the clinical relevance of undifferentiated tumour cells in astrocytic gliomas we employed a large tumour tissue microarray (n = 283) with corresponding clinical data and analyzed the expression of Nestin and Sox-2, which mark undifferentiated stem- and progenitor cells in the normal brain.Both markers were expressed abundantly and staining of nestin significantly increased with WHO grade. Further, nestin and Sox-2 immunoreactivity was significantly associated with tumour cell proliferation and nestin expression was independently associated with poor patient survival.Our findings suggest that immature glioma cells are involved in tumour growth and tumour progression and significantly impact on patient prognosis.
Gesehen am 15.11.2022